EXPLORING THE POTENTIAL OF RED KIDNEY BEANS (PHASEOLUS VULGARIS L.) TO DEVELOP PROTEIN BASED PRODUCT FOR FOOD APPLICATIONS - I. Hayat; A. Ahmad; A. Ahmed; S. Khalil; M. Gulfraz (Journal of Animal and Plant Sciences, 2014)
Protein isolate was prepared from red kidney beans and its functional properties were evaluated at different pH levels to access its suitability for food applications. Carbohydrates, crude protein, crude fiber, crude fat and ash contents of red kidney bean seeds were found to be 53.02±1.14%, 25.78±0.77%, 6.82±0.31%, 1.92±0.15% and 4.34±0.20%, respectively. Magnesium, calcium, sodium, potassium and iron were observed as macro elements in red kidney bean seeds. Protein solubility, emulsification, gelation as well as foaming properties of the bean protein isolate were significantly (P≤0.05) affected by different pH levels. The solubility, emulsifying activity and stability as well as foam capacity of the protein isolate were dependant with minimal values observed at pH 4 while maximum at pH 10. Contrarily, the stability of foam was highest at pH 4 while a decreasing trend in foam stability was observed with increase of pH. Gelation properties improved at acidic pH with maximum gelation capacity observed at pH 4 while these properties decreased at alkaline conditions. Conclusively, red kidney beans can be utilized to prepare protein isolate whose functional properties can be modified by changing the pH of the environment for better utilization in the food formulation systems.
Keywords: Kidney bean; protein isolate; protein solubility; emulsification; gelation; foaming